Pengaruh Customer Engagement dan Service quality terhadap Customer loyalty pada Pelanggan Common Folks Posbloc Medan - Ghaly Rizky Nugroho; Riza Fanny Meutia (Universitas Medan Area, 2026)
This study aims to analyze the effect of customer engagement and service quality on customer loyalty among Common Folks Posbloc Medan customers. The research problem focuses on the suboptimal level of customer engagement and service quality, which may affect customer loyalty amid increasing competition among coffee shops in Medan. This study employs a quantitative approach with an associative research design, based on the relationship marketing perspective to explain the importance of long-term relationships between companies and customers. The population consisted of 14,046 Common Folks Posbloc Medan customers during the period of July 2024 to June 2025. The sample included 99 respondents selected using the Slovin formula and purposive sampling technique. Data were collected through a Google Form questionnaire and analyzed using SPSS 25 through validity testing, reliability testing, classical assumption testing, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that customer engagement has a positive and significant effect on customer loyalty. Service quality also has a positive and significant effect on customer loyalty. Simultaneously, customer engagement and service quality have a positive and significant effect on customer loyalty. The Adjusted R Square value of 0.492 indicates that customer engagement and service quality explain 49.2% of the variation in customer loyalty, while the remaining 50.8% is explained by other factors outside the research model. These findings indicate that customer loyalty at Common Folks Posbloc Medan can be improved by strengthening customer engagement and consistently enhancing service quality.